Implementasi Manajemen Kearsipan pada PT. Semesta Mitra Sejahtera Pekanbaru Provinsi Riau - Muhammad Fadhil Ajni; Martha Hasanah Rustam (Badan Penerbitan Fakultas Pertanian Universitas Ratu Samban, 2025)
Archives are a collection of letters or documents that contain meaning and are useful for both organizational and individual interests which are stored in such a way that they can be easily found again when needed. If the archives owned are not managed properly, it can result in difficulties in retrieving the necessary archives, which can hinder further work. The aim of the research is to find out how it is implemented and the obstacles faced in implementing Archives Management at PT. Semesta Mitra Sejahtera Pekanbaru. The author's writing method is: The data type consists of primary data and secondary data. The data collection methods used were interviews and observation. Descriptive data analysis, namely describing an object as it is at a certain time. Implementation of Archives Management at PT. Semesta Mitra Sejahtera Pekanbaru uses an Alphabetical System, Number or Code System and Date System, as well as a series of activities for organizing, storing and maintaining archives. obstacles faced in the implementation of Archives Management at PT. Semesta Mitra Sejahtera Pekanbaru is the lack of adequate facilities for managing archives, the absence of special staff to manage archives and the absence of a special room for storing archives. Based on the results of the writing that the author has done, it can be concluded that in the implementation of Archives Management at PT. Semesta Mitra Sejahtera Pekanbaru is not yet running optimally. This is evidenced by the lack of order in archival storage due to the lack of a special place for archival storage. The advice that the author can give is to add adequate facilities related to archiving activities so that archive management runs well.